Macro Modelling with Many Models - Ida Wolden Bache; James Mitchell; Francesco Ravazzolo; Shaun P. Vahey (Norges Bank, 2009)
We argue that the next generation of macro modellers at Inflation Targeting central banks should adapt a methodology from the weather forecasting literature known as `ensemble modelling'. In this approach, uncertainty about model specifications (e.g., initial conditions, parameters, and boundary conditions) is explicitly accounted for by constructing ensemble predictive densities from a large number of component models. The components allow the modeller to explore a wide range of uncertainties; and the resulting ensemble `integrates out' these uncertainties using time-varying weights on the components. We provide two examples of this modelling strategy: (i) forecasting inflation with a disaggregate ensemble; and (ii) forecasting inflation with an ensemble DSGE.
hdl:11250/2497627
Keywords: C11; C32; C53; E37; E52; 330; DSGE models; ensemble modelling; forecasting; density combination